Oral health status of 6- and 12-year-old children of Roma origin from Eastern Slovakia: a pilot study - Pilát, Zuzana; Gaľová, Jana; Petrejčíková, Eva; Mathia, Matúš; Boroňová, Iveta; Bernasovská, Jarmila (Central European Journal of Public Health, 2020)
OBJECTIVE: The purpose of this study was to determine the prevalence and clinical effect of untreated dental caries in Roma children from eastern Slovakia using dmft/DMFT index and SiC index, association between dental caries development and oral hygiene, dietary habits and preventive dental care. METHODS: Dental caries were assessed by recording the dmft index (for primary dentition) and the DMFT index (for permanent dentition) that are used to assess the state of teeth, which expresses the current state of teeth or its development in an individual or the entire population. The SiC index was calculated as the mean dmft of one-third of the population with highest caries scores. The normality of data distribution was tested by Shapiro-Wilk test. P-value < 0.05 was considered statistically significant. Chi-square test was used to compare proportions (oral hygiene, dietary habits and preventive dental visit). Data were analysed using ordered logistic regression and t-test. The study includes questionnaire containing 5 questions about dietary habits, oral hygiene and preventive dental visit. RESULTS: The results of presented study confirmed higher average values of DMFT (3.24) in the population of 12-year-old Roma children and lower average values of dmft (2.5) in the second group (p < 0.05). The value of SiC index represented 6.10 in the group of six-year-old and 7.66 in twelve-year-old children. Logistic regression was performed to test the magnitude of the association between dental caries and related factors. There was statistically significant association between average value dmft/DMFT and dietary habits, oral hygiene, and preventive dental visit in both study groups. CONCLUSION: The study revealed insufficient oral hygiene of the Roma children population. Systematic implementation of preventive examinations for oral hygiene and health programmes are needed to promote oral health. The study represents a pilot study of the SiC index values in Roma minority population from eastern Slovakia.
Keywords: Romové; DMF Index; Cross-Sectional Studies; Pilot Projects; Humans; Prevalence; Slovakia; Dental Caries; zubní kaz; Slovenská republika; orální zdraví; průřezové studie; Oral Health; lidé; prevalence; dítě; pilotní projekty; Child; Roma